The Ilses urban sociology approach How to design a 20th century metropolis - Nicosia, Corina (Urban, 2016)
IntroductionIt is still a topical matter because of the spending review (2013) introduced ‘metropolitan cities’ in the Italian legal system. Urban planners and, in general, those who describe territorial dynamics had understood, since the Sixties, that the overturning of the concept of ‘territory’ made difficult identifying the territorial dimension of development policies. Using the word ‘territory’ we were used to refer to that portion of land chose by a community by defining boundaries and drawing up their own laws, but changing the daily experience of territory the spatial extension of the institution did not correspond to the spatial extension daily experienced by the community.How can we represent these spaces? How can we manage their dynamics? These were the key issues for urban planners and nowadays these issues become again relevant. We can rewrite the starting question: how to design a 21st century metropolis? KeywordsIlses; urban sociology; metropolis; city region; Sixties